2022
DOI: 10.1002/solr.202200060
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Pure Engineering for Efficient and Stable Formamidinium‐Based Perovskite Solar Cells

Abstract: Figure 10. a) UV-Vis absorbance of the FAPbI y Br 3Ày perovskites with varying y, measured in an integrating sphere. Reproduced with permission. [16] Copyright 2014, The Royal Society of Chemistry. b) Effective charge carrier mobilities of mixed-halide FAPb(Br y I 1Ày ) 3 perovskite films of varying bromide content. The solid line is a guide to the eye. Full width at half maximum (FWHM) of the PL emission peak versus bromide content. Reproduced with permission. [131] Copyright 2015, Wiley-VCH. c) Scheme of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 219 publications
(436 reference statements)
0
17
0
Order By: Relevance
“…Later on, Binek et al have shown that the black perovskite phase was stabilized at room temperature for as little as 15% MA content 46 . In addition, the authors have tentatively suggested that owing to the large dipole moment of MA, its addition reduces the formation energy for FA/MA perovskites, improves the moisture stability of FAPbI 3 and inhibits phase separation 46,47 . PSCs based on the composition (FA 1-x MA x PbI 3 or FA 1-x MA x PbI 3-…”
Section: Predicting Stability Of Perovskite Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, Binek et al have shown that the black perovskite phase was stabilized at room temperature for as little as 15% MA content 46 . In addition, the authors have tentatively suggested that owing to the large dipole moment of MA, its addition reduces the formation energy for FA/MA perovskites, improves the moisture stability of FAPbI 3 and inhibits phase separation 46,47 . PSCs based on the composition (FA 1-x MA x PbI 3 or FA 1-x MA x PbI 3-…”
Section: Predicting Stability Of Perovskite Phasesmentioning
confidence: 99%
“…The incorporation of layered two dimensional (2D) perovskites is another available option to stabilize black FAPbI 3 . Although these 2D perovskites on their own possess exceptional stability, their efficiency is still lagging behind their 3D counterparts, mainly due to the limited out-of-plane charge transport ability caused by the bulky organic cations 47 . However, when the layered perovskites are used as capping layers on top of 3D perovskites or inserted into the grain boundaries of 3D perovskites (Figure 7a & 7b), they can stabilize the cubic FAPbI 3 phase with excellent device performance and stability.…”
Section: Journal Of Materials Chemistry C Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, organic–inorganic hybrid perovskite has been considered a promising low-cost renewable photovoltaic material due to its low manufacturing cost, adjustable band gap, and excellent optical performance. It has been widely used in solar cells, light-emitting diodes, photodetectors, and so on. With the explosive growth of related research, the power conversion efficiency (PCE) of perovskite solar cells (PSCs) has increased from 3.8 to 25.7% in the last 15 years. In planar perovskite solar cell devices, the electron transport layer (ETL) plays an important role in carrier transport. , The PCE development of PSCs is strongly influenced by the open-circuit voltage ( V OC ); therefore, charge extraction and transport at the perovskite/ETL interface is crucial to improving the performance of PSC. , …”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, organic–inorganic hybrid perovskite solar cells (PSCs) have been considered as one of the most promising photovoltaic materials, mainly due to their advantages of large absorption coefficients (∼10 5 cm –1 ), tunable band gaps, and large carrier diffusion lengths (>1 μm in polycrystalline films). Currently, the certified power conversion efficiency (PCE) reaches 26% for single junction PSCs, a benefit of the tremendous research efforts on perovskite composition engineering, interface engineering, and device structure optimization. Perovskite films prepared by the solution method have many defects, and most of them are concentrated at the boundary and interface, which severely reduces carrier concentration and lifetime, and results in a lower PCE and poorer stability of the PSCs. Moreover, the presence of defects induces phase transition from α-FAPbI 3 to nonphotoactive δ-FAPbI 3 in humid atmosphere, resulting the irreversible degradation of the FAPbI 3 film and reducing the lifetime of the PSCs. Furthermore, the energy level mismatch of FAPbI 3 /Spiro-OMeTAD/Au enlarges the energy loss for the charge extraction and transport process.…”
mentioning
confidence: 99%